Profile of Differentiated Learning Implementation for Improving the Quality of Learning at SDN Sambikerep II/480 Surabaya - Syarofah, Syarofah; Budiyanto, Budiyanto; Muhimmah, Hitta Alfi (Raudhah Publisher, 2025)
To become Driving School, they must show examples in implementing education, especially differentiated learning. However, in reality they experienced problems because there was not enough preparation to implement differentiated learning. The aim of this research is to find out the process of preparation, implementation and evaluation of the implementation of differentiated learning at the Penggerak School at the elementary school level, especially in SDN Sambikerep II/480 Surabaya. In this research, descriptive qualitative methods were used. Data was collected through observation, interviews, questionnaires, field notes, and documentation regarding the preparation, implementation, and evaluation of the implementation of differentiated learning in driving schools. The research results show that teachers in driving schools are trained to prepare differentiated learning to meet student needs and achieve educational goals, including the needs of the educational environment, curriculum challenges, continuous assessment, and the ability to create innovative learning to meet student learning needs.